Sistem Pendukung Keputusan Untuk Menentukan Siswa Calon Peserta Olimpiade Dengan Metode VIKOR dan MOORA - Tukiyat, Tukiyat; Rozali, Cristien; Djaoharman, Sulaiman (Universitas Pamulang, 2023)
Students participation at Paramarta Junior High School for the past several years in the olympic competition has received unsatisfactory result. Achievement achieved seems to be lacking because it does not have a good parameter in the selection of an honor student. The decision to vote is based solely on the results of math teacher’s deliberations. This research was intended to select the best students who will be sent to the Olympic competition in mathematics using the VIKOR (Vise Kriterijumska Optimizacija I Kompromisno) and MOORA (Multi-Objective Optimization on the basic of Ratio Analysis) methods. The research was conducted in Paramarta Junior High School with objects on students as a sample. The study sample selected based on the academic value of grade 7 (seven) of 156 students then selected by selected by the math teacher’s deliberation according to the criteria that have been established by the school before so that 8 students were obtained. Research data in the form of secondary data collected with documentation studies. The data analysis method to select one candidate participant is using VIKOR and MOORA methods. The results that obtained from both methods have the same results, 3 alternavites was selected that is a student named Arya Daffa Khalifahris with 0 VIKOR index value and 0.40 MOORA optimization value.